Factors associated with biosafety level-2 research workers' laboratory exit handwashing behaviors and glove removal compliance. Issue 4 (2nd April 2016) - Johnston, James D.; Merrill, Ray M.; Zimmerman, Grant C.; Collingwood, Scott C.; Reading, James C.
ABSTRACT: Biosafety level-2 laboratories are designated for work with human-derived samples or moderate-risk microorganisms that transmit primarily by direct contact exposures. Many laboratory procedures generate unseen droplets that contaminate workers' hands, equipment, and work surfaces. Workers' strict adherence to glove removal and handwashing is required prior to laboratory exit to prevent inadvertent transmission of pathogens to self or others. However, little is known about biosafety level-2 workers' compliance with these behaviors. In this article, glove removal and handwashing compliance upon laboratory exit were measured by direct observation of 93 biosafety level-2 research workers from 21 university laboratories. Participants completed a 41-item survey measuring social cognitive theory-based variables related to handwashing, self-reported compliance, and demographic factors. Survey items, observed exit frequency, and laboratory characteristics were evaluated for associations with handwashing compliance. Overall, observed glove removal and handwashing compliance upon laboratory exit were 43.0% (Standard Error [SE] = 2.3%), and 8.2% (SE = 1.2%), respectively, while workers' self-reported glove removal and handwashing compliance were 73.7% (SE = 3.6%) and 35.5% (SE = 4.1%), respectively. The average number of observed laboratory exits per hour was 2.8 for workers with any handwashing compliance vs. 5.4 for workers with no handwashing compliance (p = 0.0013). Among the cognitive variables, behavioral modeling by supervisors and coworkers had the strongest association with workers' compliance (slope = 3.5, SE = 1.3, p = 0.0113). Workers in laboratories with a written handwashing policy had higher compliance (Mean = 14.1%, SE = 5.9%) than workers in laboratories with no written policy (Mean = 1.1%, SE = 1.0%; p = 0.0488). Multi-faceted interventions that encourage modeling of the behavior by supervisors and coworkers, implementation of written handwashing policies, and efforts to reduce exit frequency by furnishing laboratories with necessary equipment and supplies may help improve compliance.